Using a positive deviance approach to inform farming systems redesign: A case study from Bihar, India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
We tested the methodology in Bihar, India, using survey data from 43 farms and the indicators of operating profit, soil organic matter balance, water use and dietary energy production. Positive deviant farms and practices were first identified and then recombined into a redesigned farm in consultation with farmers.